2015
DOI: 10.1007/s00247-015-3423-8
|View full text |Cite
|
Sign up to set email alerts
|

Utility of unenhanced fat-suppressed T1-weighted MRI in children with sickle cell disease — can it differentiate bone infarcts from acute osteomyelitis?

Abstract: The bone marrow signal intensity on unenhanced T1-W fat-saturated MR images is not a reliable criterion to differentiate bone infarcts from osteomyelitis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…Conversely, we found that the majority of patients with culture‐positive OM had MRI findings consistent with OM. Prior studies have shown that various imaging studies including bone scintigram, ultrasound, contrast enhanced, and unenhanced fat‐suppressed T1‐weighted MRI may not accurately and consistently distinguish between OM and VOC/bone infarction in children with SCD 21‐23 . In SCD, red marrow hyperplasia, perivascular fibrosis, and hemosiderosis lead to baseline marrow signal alterations on MRI further complicating detection of superimposed infarction and/or infection 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, we found that the majority of patients with culture‐positive OM had MRI findings consistent with OM. Prior studies have shown that various imaging studies including bone scintigram, ultrasound, contrast enhanced, and unenhanced fat‐suppressed T1‐weighted MRI may not accurately and consistently distinguish between OM and VOC/bone infarction in children with SCD 21‐23 . In SCD, red marrow hyperplasia, perivascular fibrosis, and hemosiderosis lead to baseline marrow signal alterations on MRI further complicating detection of superimposed infarction and/or infection 7 .…”
Section: Discussionmentioning
confidence: 99%
“…16 These children are also at increased risk for bone infection secondary to immunosuppression from poor splenic function and chronically poor bone vascularization. 38 Bone infarction is the most common cause of hospitalization in the affected patients, 39 and it can represent an uncommon cause of acute limp when the lower extremity is affected.…”
Section: Diaphyseal Bone Infarcts Secondary To Hemoglobinopathymentioning
confidence: 99%
“…16 MRI is the most reliable technique for evaluating bone abnormalities in sickle-cell disease. 38 Jain et al 40 proposed that noncontrast T1-weighted MRI appearances accurately distinguish between osteomyelitis and sickle-cell disease, but a subsequent study refuted this statement. 38 Conventional radiographs are often normal or show subtle, nonspecific soft tissue edema during early stages of the disease.…”
Section: Diaphyseal Bone Infarcts Secondary To Hemoglobinopathymentioning
confidence: 99%
See 2 more Smart Citations